2003
DOI: 10.1021/ac034773s
|View full text |Cite
|
Sign up to set email alerts
|

Molding of Hydrogel Microstructures to Create Multiphenotype Cell Microarrays

Abstract: The fabrication of mammalian cell-containing poly(ethylene glycol) (PEG) hydrogel microstructures on glass and silicon substrates is described. Using photoreaction injection molding in poly(dimethylsiloxane) microfluidic channels, three-dimensional hydrogel microstructures encapsulating cells (fibroblasts, hepatocytes, macrophage) were fabricated with cells uniformly distributed to each hydrogel microstructure, and the number of cells in each hydrogel microstructure was controlled by changing the cell density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 41 publications
0
114
0
Order By: Relevance
“…Previous studies in 2-D and 3-D culture work have used photolithographic techniques [31,[33][34][35], laminar flow [36,[49][50][51][52], and combinations thereof [32,53,54], to generate microarrays of photo-reactive polymers. Although these previous studies provide valuable insights into the effects of ECM signals on cell behavior, photolithographic techniques are typically limited to the use of photo-reactive polymers, and laminar flow is dimensionally limited to micro-scale materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in 2-D and 3-D culture work have used photolithographic techniques [31,[33][34][35], laminar flow [36,[49][50][51][52], and combinations thereof [32,53,54], to generate microarrays of photo-reactive polymers. Although these previous studies provide valuable insights into the effects of ECM signals on cell behavior, photolithographic techniques are typically limited to the use of photo-reactive polymers, and laminar flow is dimensionally limited to micro-scale materials.…”
Section: Discussionmentioning
confidence: 99%
“…Photolithographic methods have been used to generate spatially patterned hydrogel structures, in which distinct regions contain specific cell types [31], cell adhesion ligands [32] or ECM chemistries [33,34]. For example, Pishko and coworkers have used photopolymerization within channels [35] or spots [32] to generate PEG microstructures, and demonstrated that multiple mammalian cell types remain viable in spatially patterned hydrogels for up to 7 days. Other recent studies have used microfluidic systems to generate cell-laden peptide-based hydrogels [36].…”
Section: Introductionmentioning
confidence: 99%
“…Such advances allow the introduction of spatially specific cues in hydrogels, making multicellular constructs, either through co-cultures or multilineage differentiation, a possibility [16][17][18] . Spatial patterning of hydrogels also provides an additional tool for the development of high-throughput screening technology for the rapid investigation of cell-material interactions [19][20][21][22] .…”
Section: Static Hydrogels That Mimic Biophysical Cuesmentioning
confidence: 99%
“…Although it is possible to UV crosslink PEG pre-polymer inside microchannels, 11,17,18 the direct crosslinking of the PEG polymer within microfluidic channels has not been shown to generate features with both exposed and non-exposed substrates. Therefore, we hypothesized that the molding of the PDMS stamp on a polymer film would allow for more control over the features of the microfluidic channel.…”
Section: Fabrication Of the Devicementioning
confidence: 99%